A BTMN-ES TANULÓK HELYZETÉNEK ALAKULÁSA A VAJDA MÁRTA ÓVODA, ÁLTALÁNOS ISKOLA, SZAKISKOLA, KÉSZSÉGFEJLESZTŐ ISKOLA, EGYSÉGES GYÓGYPEDAGÓGIAI MÓDSZERTANI INTÉZMÉNY ELLÁTÁSI TERÜLETÉN - Fábián Lívia (2021)
In my thesis I examined the changes in the status of the lower grade students who have difficulties with integration, learning and attitude (Hungarian acronym is: BTMN), and the approach their majority educators to these difficulties. The mentioned educators teaching in the care area of the Vajda Márta Preschool, Elementary School, Technical School, Skills Develeopment School, Integrated Institution for Special Education. The main goal of my research was to explore whether the majority of the lower grade students BTMN status is maintained or eliminated because the problems have been resolved or the student diagnosed with SNI (it means students with special educational needs) because their problems have worsened. My further pourpose was to discover whether most educators because of their BTMN status, admit students to a higher grade even if they did not deserve it because of their performance. To execute my research, on the one hand, I chose the written questioning in the form of an online questionnaire, with which I asked the teachers of 5 elementary schools. On the other hand, I chose the oral questioning in the form of an interview. I did an interview with the Deputy Director of the Member Institution of VMPSZ in Pápa. My hypotheses were confirmed as follows: For the majority of BTMN students, the classification will not be removed, after the reviews the most of students will remain in this category. At the end of the year, some educators will transfer the majority of BTMN students to a higher grade because of their status, even if they do not deserve it because of their performance.